2016
DOI: 10.1007/s13142-016-0428-2
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity interventions to promote positive youth development among indigenous youth: a RE-AIM review

Abstract: Physical activity (PA) programs are a promising strategy to promote positive youth development (PYD). It is not known if published reports provide sufficient information to promote the implementation of effective PYD in indigenous youth. The purpose of this study was to assess the extent to which published literature on PA programs that promote PYD in indigenous youth report on RE-AIM (reach, effectiveness, adoption, implementation, maintenance) indicators. A systematic literature search was conducted to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…For Indigenous youth, low contact sports may be an alternative that is supportive of participation across ages, genders, and abilities (Ruhanen & Whitford, 2011). More inclusive physical activity and sport opportunities may be especially important in rural and remote communities where programming sustainability is dependent upon increasing the number of youth involved (Baillie et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For Indigenous youth, low contact sports may be an alternative that is supportive of participation across ages, genders, and abilities (Ruhanen & Whitford, 2011). More inclusive physical activity and sport opportunities may be especially important in rural and remote communities where programming sustainability is dependent upon increasing the number of youth involved (Baillie et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Indigenous youth also recognized that limited access to physical activity and sport opportunities acted as a barrier. For some Indigenous youth, place of residence was a significant barrier, whether opportunities were limited because of the rural or remote location of the community (Baillie et al, 2016;Byrnes et al, 2015) or the socioeconomic status of the urban neighbourhood they resided in (Kerpan & Humbert, 2015). Even when opportunities were physically accessible, access to transportation and the cost of the activity were commonly mentioned communitylevel barriers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RE-AIM is intended to improve the balance between internal and external validity when developing interventions and to inform typical community and clinical organizations on the potential applicability of a given study and intervention to local settings and populations. Baillie and colleagues' summary of literature on physical activity promotion as a tool for positive youth development demonstrated that low reporting across RE-AIM dimensions makes it difficult to understand the potential generalizability of these interventions to underserved indigenous populations in Canada [16]. The use of RE-AIM also demonstrates the complexity of translational physical activity research where research can be focused on intervening at any one level of RE-AIM while assessing other dimensions as secondary outcomes.…”
Section: Physical Activity Promotion and Translational Researchmentioning
confidence: 99%